Comparative analysis of plan quality and delivery efficiency: ZAP-X vs. CyberKnife for brain metastases treatment - Niu, Ying; Rashid, Abdul; Lee, Jui-min; Carrasquilla, Michael; Conroy, Dylan R.; Collins, Brian T.; Satinsky, Andrew; Unger, Keith R.; Pang, Dalong (Frontiers in Oncology, 2024)
Purpose/Objectives ZAP-X, a novel and dedicated radiosurgery (SRS) system, has recently emerged, while CyberKnife has solidified its position as a versatile solution for SRS and stereotactic body radiation therapy over the past two decades. This study aims to compare the dosimetric performance and delivery efficiency of ZAP-X and CyberKnife in treating brain metastases of varying target sizes, employing circular collimation. Methods and materials Twenty-three patients, encompassing a total of 47 brain metastases, were included in the creation of comparative plans of ZAP-X and CyberKnife for analysis. The comparative plans were generated to achieve identical prescription doses for the targets, while adhering to the same dose constraints for organs at risk (OAR). The prescription isodose percentage was optimized within the range of 97–100% for each plan to ensure effective target-volume coverage. To assess plan quality, indices such as conformity, homogeneity, and gradient (CI, HI, and GI) were computed, along with the reporting of total brain volumes receiving 12Gy and 10Gy. Estimated treatment time and monitor units (MUs) were compared between the two modalities in evaluating delivery efficiency. Results Overall, CyberKnife achieved better CI and HI, while ZAP-X exhibited better GI and a smaller irradiated volume for the normal brain. The superiority of CyberKnife’s plan conformity was more pronounced for target size less than 1 cc and greater than 10 cc. Conversely, the advantage of ZAP-X’s plan dose gradient was more notable for target sizes under 10 cc. The homogeneity of ZAP-X plans, employing multiple isocenters, displayed a strong correlation with the target’s shape and the planner’s experience in placing isocenters. Generally, the estimated treatment time was similar between the two modalities, and the delivery efficiency was significantly impacted by the chosen collimation sizes for both modalities. Conclusion This study demonstrates that, within the range of target sizes within the patient cohort, plans generated by ZAP-X and CyberKnife exhibit comparable plan quality and delivery efficiency. At present, with the current platform of the two modalities, CyberKnife outperforms ZAP-X in terms of conformity and homogeneity, while ZAP-X tends to produce plans with a more rapid dose falloff.